2020
DOI: 10.1186/s12864-020-6488-1
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of horseshoe crab Tachypleus tridentatus reveals its evolutionary scenario and well-developed innate immunity

Abstract: Background: Horseshoe crabs are ancient marine arthropods with a long evolutionary history extending back approximately 450 million years, which may benefit from their innate immune systems. However, the genetic mechanisms underlying their abilities of distinguishing and defending against invading microbes are still unclear.Results: Here, we describe the 2.06 Gbp genome assembly of Tachypleus tridentatus with 24,222 predicted proteincoding genes. Comparative genomics shows that T. tridentatus and the Atlantic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 83 publications
2
18
0
Order By: Relevance
“…Spiders and scorpions, on the other hand, possess two Hox clusters due to one round of whole-genome duplication that occurred in their common ancestor (Schwager et al, 2017). Sequencing of the whole-genome of T. tridentatus, a species closely related to T. gigas, showed that it contained two Hox clusters, suggesting one round of whole-genome duplication in this lineage (Gong et al, 2019;Zhou et al, 2020). However, a recent study involving sequencing and analysis of the genome of C. rotundicauda revealed the presence of five Hox clusters (Shingate et al, 2020), which suggested at least two rounds of whole-genome duplication.…”
Section: Protein-coding Genesmentioning
confidence: 99%
“…Spiders and scorpions, on the other hand, possess two Hox clusters due to one round of whole-genome duplication that occurred in their common ancestor (Schwager et al, 2017). Sequencing of the whole-genome of T. tridentatus, a species closely related to T. gigas, showed that it contained two Hox clusters, suggesting one round of whole-genome duplication in this lineage (Gong et al, 2019;Zhou et al, 2020). However, a recent study involving sequencing and analysis of the genome of C. rotundicauda revealed the presence of five Hox clusters (Shingate et al, 2020), which suggested at least two rounds of whole-genome duplication.…”
Section: Protein-coding Genesmentioning
confidence: 99%
“…As a group of living fossil, horseshoe crabs in morphology have barely changed in the past 200 million years. Previous studies have shown that its hemolymph contains a rich repertoire of innate immune molecules, so horseshoe crab is a useful invertebrate model for exploring the innate immune mechanism (7)(8)(9)(10)(11). The resistance of horseshoe crabs to pathogenic invasion depends entirely on the hard carapace and the innate immune system including humoral and cellular responses (2).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of long-read DNA and Hi-C sequencing was successful in resolving a large and highly repetitive insect genome. To date, this is the largest insect genome and one of the largest arthropod genomes assembled to chromosome scale, the horseshoe crab's (Tachypleus tridentatus) being only slightly larger (2.06 Gb vs 2.05 Gb) (Zhou et al 2020). This is remarkable because the assembly of relatively large and highly repetitive insect genomes into highly contiguous ones such as this was previously unattainable (Li et al 2020).…”
Section: Discussionmentioning
confidence: 97%